2007
DOI: 10.1007/s00401-007-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced striatal tyrosine hydroxylase in incidental Lewy body disease

Abstract: Incidental Lewy body disease (ILBD) is the term used when Lewy bodies are found in the nervous system of subjects without clinically documented parkinsonism or dementia. The prevalence of ILBD in the elderly population has been estimated at between 3.8 and 30%, depending on subject age and anatomical site of sampling. It has been speculated that ILBD represents the preclinical stage of Parkinson's disease (PD) and/or dementia with Lewy bodies (DLB). Studies of ILBD could potentially identify early diagnostic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 47 publications
6
90
0
Order By: Relevance
“…All subjects with Lewy body disorders must pass through an ILBD phase, however. Despite the apparently low conversion of ILBD to PD or DLB, it would appear that ILBD is not a completely benign condition, as it is associated with an approximately 50% decrease in striatal dopaminergic markers as well as the clinical biomarker of hyposmia [6063]. …”
Section: Discussionmentioning
confidence: 99%
“…All subjects with Lewy body disorders must pass through an ILBD phase, however. Despite the apparently low conversion of ILBD to PD or DLB, it would appear that ILBD is not a completely benign condition, as it is associated with an approximately 50% decrease in striatal dopaminergic markers as well as the clinical biomarker of hyposmia [6063]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies showed that motor signs of PD manifest after the loss of approximately 50% of nigral neurons and 80% of striatal dopamine [4,47]. Two postmortem studies using more rigorous quantitative methods, such as using a tessellation method [17] and dissector-based neuromorphometry [27], found that about 30% of nigral neuronal loss appeared sufficient to cause motor symptoms in PD [2]. However, recent research suggests that the first symptoms of Parkinson's disease may manifest after just a 20% decrease in the number of dopaminergic neurons SNc, which has been shown in animal models where a reduction of about 14 to 23% of nigral neuron count or 14% to 37% of striatal dopamine was sufficient to induce mild parkinsonism [43].…”
Section: Discussionmentioning
confidence: 99%
“…2,45 Recent studies have also shown that iLB cases have reduced striatal dopaminergic immunoreactive markers compared with controls, although not as reduced as in PD. [46][47][48] However, while the prevalence of PD is 1% among those older than 60 years, 49 post-mortem studies have shown that 8-14% of subjects older than 60 years without PD or dementia present iLB in the brainstem nuclei. 43,45,50,51 This 10-time higher frequency of iLB compared with the prevalence of PD may not fit with the concept that iLB cases represent a precursor of the motor stage of PD.…”
Section: Incidental Lewy Bodiesmentioning
confidence: 96%